Data visualization with Tableau - Acharya, Seema (Packt Publishing, 2018)
"Tableau is a Data Visualization tool for molding information into various visuals. This course gives an overview of the fundamentals, from normal computations to implementations of various concepts such as Integrating Tableau with R, advanced graphs, and formatting visualizations. This video course takes you on a journey in which you'll master data visualization using Tableau by getting to know valuable methods for utilizing advanced calculations to solve complex problems. These techniques include the creative use of different types of calculation such as row-level, aggregate-level, and more. You will discover how almost any data visualization challenge can be met in Tableau by a proper understanding of the tool's inner workings and creatively exploring its possibilities. By the end of the course you will be equipped for success as a Data Analyst: you will be able to create effective dashboards and data visualization solutions using Tableau."--Resource description page